Mind games (BOOK) (pub date 5/21/2024) (St. Martin's Press, 2024)
"As they do each June, the Foxes have driven the winding roads of Appalachia to drop off their children for a two-week stay at their grandmother's. Here, twelve-year-old Thea can run free and breathe in the smells of pine and fresh bread and Grammie's handmade candles. But as her parents head back to suburban Virginia, they have no idea they're about to cross paths with a ticking time bomb. Back in Kentucky, Thea and her grandmother Lucy both awaken from the same nightmare. And though the two have never discussed the special kind of sight they share, they know as soon as their tearful eyes meet that something terrible has happened. The kids will be staying with Grammie now in Redbud Hollow, and thanks to Thea's vision, their parents' killer will spend his life in supermax. Over time, Thea will make friends, build a career, find love. But that ability to see into minds and souls still lurks within her, and though Grammie calls it a gift, it feels more like a curse-because the inmate who shattered her childhood has the same ability. Thea can hear his twisted thoughts and witness his evil acts from miles away. He knows it, and hungers for vengeance. A long, silent battle will be waged between them--and eventually bring them face to face, and head to head."--

Middle of the night (BOOK) (pub date 6/18/2024): a novel (Dutton, an imprint of Penguin Random House LLC, 2024)
"In the latest jaw-dropping thriller from New York Times bestselling author Riley Sager, a man must contend with the long-ago disappearance of his childhood best friend-and the dark secrets lurking just beyond the safe confines of his picture-perfect neighborhood"--

Resurrection (BOOK) (pub date 6/25/2024): a novel (Delacorte Press, 2024)
Description Not Provided

How to sell a haunted house (Berkley, 2023)
"New York Times bestselling author Grady Hendrix takes on the haunted house in a hilarious and terrifying new novel that explores the way your past-and your family-can haunt you like nothing else.... Louise's parents have passed away, and she's returning to the small Southern town where she grew up to get their house ready to sell. It means she'll have to spend time with her younger brother-and their old grudges make that a terrifying prospect. But childhood hurts pale in comparison to the dangers posed by what still lives inside the house"--

Long Island (pub date 5/7/2024): a novel (Scribner, 2024)
"Eilis Lacey is Irish, married to Tony Fiorello, one of four Italian American brothers, all of whom live in neighboring houses on a cul-de-sac in Lindenhurst, Long Island, with their wives and children and Tony's parents, a huge extended family that lives and works, eats and plays together. It is the spring of 1976 and Eilis, now in her forties with two teenage children, has no one to rely on in this still-new country. Though her ties to the town in Ireland where she grew up remain stronger than those that hold her to her new land and home, she has not returned in decades. One day, when Tony is at his job, an Irishman comes to the door asking for her by name. He tells her that his wife is pregnant with Tony's child, and that when the baby is born, he will not raise it but instead will deposit it on Eilis's doorstep. It is what Eilis does - and what she refuses to do - in response to this stunning news that makes Tóibín's novel so riveting. Long Island is about longings unfulfilled, even unrecognized. The silences in Eilis's life are thunderous and dangerous, and there's no one defter than Tóibín at giving them language. This is a gorgeous story of a woman alone in a marriage and the deepest of bonds she rekindles on her return to the place and people she left behind, to ways of living and loving she thought she'd lost. Eilis is perhaps Tóibín's most moving and unforgettable character, and this novel is a masterpiece"--

Husbands & lovers (BOOK) (pub date 6/25/24): a novel (Ballantine Books, 2024)
"Connecticut, 2022. Mallory Dunne has spent her life trying to be a good mother to her son, Sam. Raising him alone is hard, even with the help of her sister. Two years ago, Sam ingested a toxic mushroom and fell into a coma. Now recovered, he needs a new kidney to live a normal life, forcing Mallory to track down his father in the hope that they're a match. Her journey to find him again transports her back to the summer they spent on the paradise of Winthrop Island - a time of music, porch cocktails, young love, and the site of a terrible event that drove Mallory from his arms. Cairo, 1951. Hannah Ainsworth cannot escape the war that destroyed her life, her first love - and her hope for a brighter future. A Hungarian émigré married to a hapless Britishman working for the Foreign Office, Hannah is thrown into the parched but bustling desert landscape of Egypt, now convulsing with revolution. Looking for passion, she begins a dangerous affair with an enigmatic hotel manager who shows her the majesty of the pyramids and his nation. But their newfound romance has perilous consequences, and Hannah must decide how much she's willing to risk for the pursuit of love. Mallory's moving journey to protect her son intertwines with Hannah's explosive affair in surprising, illuminating ways. Husbands & Lovers is the epic story of two fierce women united by an heirloom, passed down to Mallory by her own mother - a cobra bracelet with a mysterious provenance, studded with gems and secrets"--

Garvey's choice: the graphic novel (Wordsong, an imprint of Astra Books for Young Readers, 2023)
"Award-winning author Nikki Grimes's beloved novel in verse Garvey's Choice is now a graphic novel, imaginatively and dramatically illustrated by Little Shaq artist Theodore Taylor III."

The Hazelbourne ladies motorcycle and flying club (pub date 5/7/2024): a novel (The Dial Press, 2024)
"Constance Haverhill is without prospects. Her mother has just passed away, her brother is newly married, and now that the Great War is over, she has been asked to give up managing the estate she helped to run when the men all joined the army. It is suggested to her that she become a governess. But first, she will act as caretaker to Mrs. Fog, an old family friend who is convalescing at a seaside resort. Constance is soon swept up in the social whirl of the Meredith Hotel and its colorful inhabitants, most notably, Poppy Wirrall. Poppy wears trousers, operates a taxi and delivery service to employ local women, and manages a ladies' motorcycle club. She and her friends welcome Constance into their circle, despite the differences in their stations-Poppy is, for all her empowered modernity, the daughter of a land-owning gentleman, while Constance has only weeks before she must find a position and a home. Constance soon learns, however, that not everything is as it seems in this pocket of English high society. As her connection to this new group deepens and she makes a powerful impression on Poppy's recalcitrant but handsome brother-a former fighter pilot who recently lost a leg in battle-old secrets come to light. Soon, the women are forced to confront the fact that the freedoms they gained during the war are likely to be revoked as the country settles into a hard-won peace"--

Tell me everything (pub date 8/13/2024): a novel (Random House, 2024)
"With her "extraordinary capacity for radical empathy" (The Boston Globe), remarkable insight into the human condition, and silences that contain multitudes, Elizabeth Strout returns to the town of Crosby, Maine, and to her beloved cast of characters as they deal with a shocking crime in their midst; fall in love and yet choose to be apart; and grapple with the question, as Lucy Barton puts it: What does anyone's life mean? It's autumn in Maine, and the town lawyer Bob Burgess has become enmeshed in an unfolding murder investigation, defending a lonely, isolated man accused of killing his mother. He has also fallen into a deep and abiding friendship with the acclaimed writer, Lucy Barton, who lives down the road in a house by the sea with her husband, William. Together, Lucy and Bob go on walks and talk about their lives, their fears and regrets, and what might have been. Lucy, meanwhile, is finally introduced to the iconic Olive Kitteridge, now living in a retirement community on the edge of town. Together, they spend afternoons in Olive's apartment, telling each other stories. Stories about people they have known - "unrecorded lives," Olive calls them - reanimating them, and, in the process, imbuing their lives with meaning"--

Counting miracles (pub date 9/24/2024): a novel (Random House, 2024)
"From the acclaimed author of The Longest Ride and The Notebook comes an emotional, powerful novel about wondering if we can change-or even make our peace with-the path we've taken. Tanner Hughes was raised by his grandparents, following in his grandfather's military footsteps to become an Army Ranger. His whole life has been spent abroad, and he is the proverbial rolling stone: happiest when off on his next adventure, zero desire to settle down. But when his grandmother passes away, her last words to him are find where you belong. She also drops a bombshell, telling him the name of the father he never knew-and where to find him. Tanner is due at his next posting soon, but his curiosity is piqued, and he sets out for Asheboro, North Carolina, to ask around. He's been in town less than twenty-four hours when he meets Kaitlyn Cooper, a doctor and single mom. They both feel an immediate connection; Tanner knows Kaitlyn has a story to tell, and he wants to hear it. To Kaitlyn, Tanner is mysterious, exciting-and possibly leaving in just a few weeks. Meanwhile, nearby, eighty-three-year-old Jasper lives alone in a cabin bordering a national forest. With only his old dog, Arlo, for company, he lives quietly, haunted by a tragic accident that took place decades before. When he hears rumors that a white deer has been spotted in the forest-a creature of legend that inspired his father and grandfather-he becomes obsessed with protecting the deer from poachers. As these characters' fates orbit closer together, none of them is expecting a miracle . . . but that may be exactly what is about to alter their futures forever"--

The glassmaker (BOOK) (pub date 6/18/2024) (Viking, 2024)
"In 1486, Orsola Rosso is the eldest daughter in a family of glassblowers in Murano, Italy. As a woman, she is not meant to blow glass-but when her father dies, she teaches herself to make beads in secret, and her work becomes the cornerstone of the Rosso family fortunes. Skipping like a stone through the centuries, we follow Orsola and her family as they live through creative triumph and heartbreaking loss, from a plague rearing its head over Venice to Continental soldiers stripping its palazzos bare, from the domination of Murano and its maestros to the transformation of the city of trade into a city of tourists. In every era, the Rosso women ensure that their work, and their bonds, endure"--

The lost coast (pub date 8/6/2024): a novel (Ballantine Books, 2024)
"It's been almost a year since Clay Edison was forced out of his job at the coroner's bureau. Now he's on his own, working as a private eye, scraping by. Clay is brought a fraud case that begins with a man surprised to learn that he's been named the executor of his grandmother's estate. Her accounts are a mess, and not everything is adding up. He's at the end of his rope and needs Clay's expertise. As Clay dives deeper into a decades-old scheme targeting the vulnerable, his investigation leads him to a bizarre town buried in the remote California wilderness. The residents don't care much for outsiders. They certainly don't like Clay asking questions. And they'll do just about anything to shut him up"--

Not in love (Berkley Romance, 2024)
"Rue Siebert might not have it all, but she has enough: a few friends she can always count on, the financial stability she yearned for as a kid, and a successful career as a biotech engineer at Kline, one of the most promising start-ups in the field of food science. Her world is stable, pleasant, and hard-fought. Until a hostile takeover and its offensively attractive front man threatens to bring it all crumbling down. Eli Killgore and his business partners want Kline, period. Eli has his own reasons for pushing this deal through--and he's a man who gets what he wants. With one burning exception: Rue. The woman he can't stop thinking about. The woman who's off-limits to him. Torn between loyalty and an undeniable attraction, Rue and Eli throw caution out the lab and the boardroom windows. Their affair is secret, no-strings-attached, and has a built-in deadline: the day one of their companies will prevail. But the heart is risky business--one that plays for keeps"--

Flashback (BOOK) (6/25/2024) (Kendra Michaels, 11,, 2024)
"When two sisters in their twenties go missing while investigating a series of brutal murders committed over two decades before, Kendra Michaels joins the search for the missing women. The sisters' mother was one of the victims, and police seem to have had little interest in actively pursuing the cold case. Armed with the box of photos, videos, police reports and notes gathered by the sisters over the years, Kendra's investigation takes her to nearby Catalina Island, a peaceful hamlet that may be hiding a grim secret. Little does Kendra realize that her search is about to unleash a long-dormant killer on modern-day San Diego. With help from government agent-for-hire Adam Lynch, private eye Jessie Mercado and her sightless childhood friend Olivia Moore, Kendra must unravel the deadly scheme not only to save the lives of the two sisters, but also untold others"--

By any other name (pub date 8/20/2024): a novel (Ballantine Books, 2024)
"A captivating novel about two women, centuries apart, fighting to be heard - one of whom may be the real author of Shakespeare's plays - from the New York Times bestselling author of Wish You Were Here. As an undergraduate, Melina Green had a rare opportunity to have one of her first plays judged by famous theater critic Jasper Tolle, only to be publicly humiliated by a harsh and biased critique. Ten years later, her confidence as a playwright has never recovered, although she has just completed a work that she thinks is her best yet. It is based on the life of her ancestor Emilia Bassano, the first published female poet in England - and rumored to be the "Dark Lady" of Shakespeare's sonnets - but whom some scholars suspect may be the real author of a number of his plays. Melina wonders if she dares risk failure again, and then her best friend takes the decision out of her hands and submits it to a festival under a male pseudonym. In 1581, the young orphan Emilia Bassano is being raised in the ways of English aristocracy by the Baron Willoughby and his sister. Her lessons on languages, reading, and writing have endowed her with a sharp wit and a gift for storytelling. But like most women of her day, she has no control over her fate, and is ripped from her old life and forced to become a courtesan to Lord Hunsdon, a man knighted by Queen Elizabeth as the Lord Chamberlain in charge of all theater in London. Though she has no other freedoms, and inspired by the work of the most brilliant playwrights of the time, she pseudonymously sets her own pen to paper to tell a story. Told in dual intertwining timelines, this sweeping tale of ambition, courage, and desire centers two women who are determined to create something beautiful despite the prejudices they face. As Emilia alters the course of her life and therefore the course of the world, she blazes a trail. Centuries later, will Melina face the same terrible fate - to have her work celebrated, but only at the price of letting another take credit?"--

The guncle abroad (pub date 5/21/24): a novel (G.P. Putnam's Sons, 2024)
"Patrick O'Hara is back. It's been five years since his summer as his niece Maisie and nephew Grant's caretaker after their mother's passing. The kids are back in Connecticut with their dad, and Patrick has relocated to New York to remain close by, and relaunch his dormant acting career. After the run of his second successful sit-com comes to a close, Patrick feels on top of the world... professionally. Some things have had to take a back seat. Looking down both barrels at fifty, Patrick is single again after breaking things off with Emory. But at least he has a family to lean on. Until that family needs to again lean on him. When his brother Greg announces he's getting remarried in Italy, Maisie and Grant are not thrilled. Patrick feels drawn to take Maisie and Grant back under his wing. As they travel through Europe on their way to the wedding, Patrick tries his best to help them understand love, much as he once helped them comprehend grief. But when they arrive in Italy, Patrick is overextended managing a groom with cold feet, his sister Clara who seems to be flirting with guests left and right, a growing rivalry with the kids' alluring soon to be launt (lesbian aunt), and two anxious kids trying desperately to adjust to a new normal all culminating in a disastrous rehearsal dinner. Can Patrick save the day? Will teaching the kids about love help him repair his own love life? Can this change of scenery help Patrick come to terms with finally growing up? Gracing the page with his signature blend of humor and heart, Steven Rowley delivers the long-awaited sequel to a beloved story, all about the complicated bonds of family, love, and what it takes to rediscover yourself, even at the ripe age of fifty"--

Look on the bright side (pub date 5/28/2024) (Berkley, 2024)
"From the author of Pack Up the Moon comes a funny, romantic, and deeply moving novel about the unexpected rewards that come from life's swerves. Lark Smith was planning a fairy-tale wedding to her high school sweetheart when, in the blink of an eye, everything she dreamed of was suddenly gone. That day, Lark decided the best way to deal with loss was to prevent others from ever having to. Five years later, her goal of becoming a doctor-the best doctor-is just within reach when, without warning, she's fired. Now getting back on track means making a deal with the devil. Well, not exactly, even if they do call renowned surgeon Lorenzo Santini "Dr. Satan" behind his back. He'll use his influence to get her back in the program. But first, Lark has to pose as his significant other all summer...his sister is getting married, and he doesn't want his ninety-nine-year-old grandmother spending her precious time worrying over his single state. What Lark doesn't realize is she's already met Lorenzo's brother Dante, the firefighter who was there on Lark's worst day. The brothers couldn't be more different...which is becoming a problem, because the last thing Lark wants is to fall in love again. While spinning white lies during one unforgettable Cape Cod summer, Lark is exposed to the truth: when life throws you in the dark, love, friends, and family are there to help you look on the bright side"--

Stuart Woods' Smolder (BOOK) (pub date 6/4/2024) (Stone Barrington novel, ,, 2024)
"In this latest adrenaline-fueled adventure in the #1 New York Times bestselling series, Stone Barrington faces his most dangerous threat yet"--

Lies and weddings: a novel (Doubleday, 2024)
"Rufus Leung Gresham, future Earl of Greshambury and son of a former Hong Kong supermodel has a problem: the legendary Gresham Trust has been depleted by decades of profligate spending, and behind all the magazine covers and Instagram stories manors and yachts lies nothing more than a gargantuan mountain of debt. The only solution, put forth by Rufus's scheming mother, is for Rufus to attend his sister's wedding at a luxury eco-resort, a veritable who's-who of sultans, barons, and oligarchs, and seduce a woman with money. Should he marry Solène de Courcy, a French hotel heiress with honey blond tresses and a royal bloodline? Should he pursue Martha Dung, the tattooed venture capital genius who passes out billions like lollipops? Or should he follow his heart, betray his family, squander his legacy, and finally confess his love to the literal girl next door, the humble daughter of a doctor, Eden Tong? When a volcanic eruption burns through the nuptials and a hot mic exposes a secret tryst, the Gresham family plans-and their reputation-go up in flames. Can the once-great dukedom rise from the ashes? Or will a secret tragedy, hidden for two decades, reveal a shocking twist? In a globetrotting tale that takes us from the black sand beaches of Hawaii to the skies of Marrakech, from the glitzy bachelor pads of Los Angeles to the inner sanctums of England's oldest family estates, Kevin Kwan unfurls a juicy, hilarious, sophisticated and thrillingly plotted story of love, money, murder, sex, and the lies we tell about them all"--

What have you done? (BOOK) (pub date 7/30/2024) (Pamela Dorman Books/Viking, 2024)
Description Not Provided